Influence of Bribery Intensity on Business Ethics Lack on Thailand’s Pharmaceutical Sector - Kerdpitak, Chayanan (Journal of Posthumanism, 2025)
A high degree of bribery and isomorphism can decrease and diminish the positive level of ethics in a business that directly influences the operational performance of the sector. However, the main goal of this research paper is to analyze the diminishing of business ethics in the pharmaceutical sector of Thailand due to the role of isomorphism dimensions which further include mimetic, coercive and competitive isomorphism. In this research study normative bribery belief, overall business constraints and competitive pressure have also been evaluated through the mediating role of bribery intensity. For this intention, almost all of the data and information of the study were collected from 360 pharmacist of different pharmaceutical firms in Thailand. The measurements of the results through SEM techniques revealed that institutional coercive is one of the strongest and significant determinants of bribery. However, the effect and impact of the pressure of isomorphic dimensions on the bribery practices and intensity vary across different pharmaceutical firms of Thailand. Thus, the given research study suggests to the managers of pharmaceutical firms that they must consider and take some significant actions for mitigating bribery in different pharmaceutical firms.